Accounting information is the basis for stable development of the world economy (Journal of Economic Research & Business Administration, 2017)
With the expansion of the circle of users of accounting information onfinancial and economic activity of the enterprise, the purpose of which isto make profit and competitiveness, significantly increases the interest ofparticipants in the economic process to objective and reliable informationabout their financial position and business activity. For the economies ofmost countries are characterized by state regulation and market controlmethods simultaneously. economic management system includes a varietyof functions. One of the most important functions is the account, whichprovides the system with the necessary information. In this regard, thearticle discusses the role of accounting information to ensure the developmentof the world economy.